Effects of a school-based physical activity intervention on children with intellectual disability: a cluster randomized trial - Michael Noetel; Taren Sanders; Danielle Tracey; David R. Lubans; Viviene A. Temple; Andrew Bennie; James Conigrave; Mark Babic; Bridget Booker; Rebecca Pagano; James Boyer; Chris Lonsdale (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Children living with disability have poorer health outcomes than their typically developing peers. They are less physically active and at increased risk of chronic disease. Teacher-led, whole-of-school physical activity interventions are promising levers for population-level change, but are seldom tested among children with disability. We aimed to evaluate the effect of a blended teacher-professional learning program (online and in-person) on fundamental movement skills (FMS) and physical activity among children with intellectual disability. Methods In this cluster randomized clinical trial, we randomized 20 government-funded primary schools, including 238 consenting students (Grades 2–5; aged 8–11 years at baseline). Ten schools received the blended teacher-professional learning intervention and 10 were assigned as waitlist controls. The professional learning was designed to support teachers as they implemented a whole-of-school intervention designed to enhance FMS and increase physical activity levels. The school-based intervention was mostly online learning, followed by lesson observations and site visits from project staff. Blinded assessors measured FMS competency using the Test of Gross Motor Development-3. Secondary outcomes were self-concept, enjoyment, wellbeing, 300-yard run time, and accelerometer-measured physical activity. Results We found no significant group-by-time effects for the primary outcome (FMS competency: b = 1.07 [95% CI -3.70, 5.84], p =.658) or any secondary outcomes. Conclusions A school-based intervention did not improve FMS competency or physical activity in children with intellectual disability. Results may be attenuated by the COVID-19 pandemic. Alternatively, low intensity teacher-professional learning interventions may not be enough to improve FMS or physical activity among children with intellectual disability. Trial registration Australian New Zealand Clinical Trials Registry registration number: ACTRN12620000405910, registered: 25/03/2020.